Personality is of central concern to understand health: towards a theoretical model for health psychology - Ferguson, Eamonn (Taylor & Francis, 2013)
This paper sets out the case that personality traits are central to health psychology. To achieve this, three aims need to be addressed. First, it is necessary to show that personality influences a broad range of health outcomes and mechanisms. Second, the simple descriptive account of Aim 1 is not sufficient, and a theoretical specification needs to be developed to explain the personality-health link and allow for future hypothesis generation. Third, once Aims 1 and 2 are met, it is necessary to demonstrate the clinical utility of personality. In this review I make the case that all three Aims are met. I develop a theoretical framework to understand the links between personality and health drawing on current theorising in the biology, evolution, and neuroscience of personality. I identify traits (i.e., alexithymia, Type D, hypochondriasis, and empathy) that are of particular concern to health psychology and set these within evolutionary cost-benefit analysis. The literature is reviewed within a three-level hierarchical model (individual, group, and organisational) and it is argued that health psychology needs to move from its traditional focus on the individual level to engage group and organisational levels.